2018
DOI: 10.15191/nwajom.2018.0606
|View full text |Cite
|
Sign up to set email alerts
|

Using the Multisensor Advected Layered Precipitable Water Product in the Operational Forecast Environment

Abstract: Gitro, C. M., and Coauthors, 2018: Using the multisensor advected layered precipitable water product in the operational forecast environment. J. Operational Meteor., 6 (6), 59-73, doi CHRISTOPHER GRASSOTTI NOAA/NESDIS Center for Satellite Applications and Research and University of Maryland, ESSIC/CICS-MD, College Park, MarylandThe Cooperative Institute for Research in the Atmosphere, via the Joint Polar Satellite System Proving Ground, developed an advectively blended layered precipitable water (ALPW) produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Discussions in theme 4 highlighted the significance of satellite-based precipitation and water vapor products in enhancing weather forecasting and societal applications over challenging terrains like Alaska. The value of various LEO precipitation products for forecasters was emphasized, including the Advected Layer Precipitable Water (ALPW; Gitro et al 2018) product, which provides insights into atmospheric water vapor distribution. The insights from the National Weather Service (NWS) Weather Forecast Offices (WFOs) and Weather Prediction Center (WPC) shed light on the critical role of low-latency precipitation products in situational awareness and short-term forecasting.…”
Section: Precipitation Estimation Users and Applicationsmentioning
confidence: 99%
“…Discussions in theme 4 highlighted the significance of satellite-based precipitation and water vapor products in enhancing weather forecasting and societal applications over challenging terrains like Alaska. The value of various LEO precipitation products for forecasters was emphasized, including the Advected Layer Precipitable Water (ALPW; Gitro et al 2018) product, which provides insights into atmospheric water vapor distribution. The insights from the National Weather Service (NWS) Weather Forecast Offices (WFOs) and Weather Prediction Center (WPC) shed light on the critical role of low-latency precipitation products in situational awareness and short-term forecasting.…”
Section: Precipitation Estimation Users and Applicationsmentioning
confidence: 99%
“…Satellites used in the initial LPW study were S-NPP, NOAA-19/20, MetOp-A/B, and Defense Meteorological Satellite Program F17/18. Advection of retrieved LPW utilizes winds from the Finite Volume Cubed Global Forecast System (FV3GFS, hereafter GFS) to create Advected Layer Precipitable Water (ALPW), which uses a technique called advective blending (Gitro et al, 2018). ALPW is computed within the following four pressure layers: (1) the surface to 850 hPa, (2) 850-700 hPa, (3) 700-500 hPa, and (4) 500-300 hPa.…”
Section: Satellite Datamentioning
confidence: 99%
“…Several examples of IDSS activities have been documented in the literature. Lindley et al (2016) demonstrated the utility of using text-and graphical-based communication strategies to alert fire weather partners of satellite-detected fire ignitions, which resulted in a more rapid and efficient response to emerging wildfire threats. IDSS has also been employed during severe weather events.…”
Section: Nwa Journal Of Operational Meteorologymentioning
confidence: 99%